Universal Free School Meals and School and Student Outcomes: A Systematic Review - Spill, Maureen K.; Trivedi, Rupal; Thoerig, Rachel C.; Balalian, Arin A.; Schwartz, Marlene B.; Gundersen, Craig; Odoms-Young, Angela; Racine, Elizabeth F.; Foster, Margaret J.; Davis, Julie S.; MacFarlane, Amanda J. (JAMA network open, 2024)
The White House National Strategy on Hunger, Nutrition, and Health included expanding free school meals to all students, regardless of income, which has sparked debate in the United States. To assess the association between universal free school meals (UFSMs) and school and student outcomes in the United States. An expert panel-informed protocol was developed to evaluate intervention or cohort studies comparing UFSM programs, such as the Community Eligibility Provision (CEP), with non-UFSM programs in US schools from August 2012 (excluding 2020-2021 due to the COVID-19 pandemic) in peer-reviewed publications or government reports. Outcomes included meal participation rates, attendance, dietary intake and quality, food waste, economic impact, food insecurity, anthropometrics, disciplinary actions, stigma, and shaming. A search of Medline, Econlit, Business Source Ultimate, ERIC, Agricola, Cab Abstracts, and CINAHL was performed in April 2024. Two researchers screened articles for inclusion, extracted data, and assessed risk of bias, using the Risk of Bias in Nonrandomized Studies of Interventions tool, for each included study. Grading of Recommendations, Assessment, Development, and Evaluations was used to assess the certainty of evidence for each outcome. The search identified 2784 records, with 6 studies included, representing more than 11 000 elementary, middle, and high schools. Nonrandomized intervention studies performed difference-in-difference or rate ratio analysis to investigate CEP participation rates, attendance, anthropometrics, and/or suspensions. CEP was associated with increased lunch (3 studies; moderate certainty) and breakfast (1 study; very low certainty) participation. School attendance was unchanged or improved in schools with CEP compared with schools without UFSM (2 studies; low certainty). CEP was associated with lower obesity prevalence (1 study; very low certainty) and fewer suspensions (1 study; very low certainty). Reasons for downgrading the certainty ratings included indirectness (data not fully representative of the United States) and inconsistency (small number of studies limiting ability to assess consistency). Despite the limitations, the evidence reflected well-designed longitudinal intervention studies appropriate for decision-making. In this systematic review, UFSMs were associated with increased meal participation, no or slight improvements in attendance, and decreased obesity prevalence and suspension rates; certainty of evidence was moderate for lunch participation and low or very low for other outcomes. Studies did not report several important outcomes, such as diet quality and food security, suggesting the need for more high-quality research encompassing policy-relevant indicators.